Immunochemical quantitation of complement components of Clq and C3 in sera and synovial fluids of patients with bone and joint diseases. Issue 3 (June 1980) - Ochi, T; Yonemasu, K; Ono, K
Abstract : The amount of the initiating complement component (Clq) in the classical pathway and the first essential component (C3) in the alternative complement pathway were measured with a single radial immunodiffusion (SRID). A high ionic strength was used corresponding to that of 0 . 25 M NaCl and 0 . 01 M EDTA to avoid nonspecific binding of Clq with immune aggregates. Measurements were made on sera and/or synovial fluids from 165 patients with various bone and joint diseases. Values of Clq and C3 in synovial fluids were also expressed as ratios to that of albumin in the same specimens to avoid the influence of differences in volume of synovial fluid in various diseases, and this appeared to provide a reliable index reflecting pathological conditions. Both serum Clq and C3 levels were raised highly in rheumatoid arthritis, gout, and osteomyelitis, but the extent of the elevation of C3 was less conspicuous. Values of Clq and C3 in synovial fluids also markedly increased in rheumatoid arthritis.